2013
DOI: 10.1111/jocn.12444
|View full text |Cite
|
Sign up to set email alerts
|

How virtual admission affects coping – telemedicine for patients with chronic obstructive pulmonary disease

Abstract: Telemedicine may result in different roles for patients, relatives and health professionals. Clinicians should consider how they can support chronic obstructive pulmonary disease patients' coping during telemedical interventions, focusing on how to ensure a sustained improvement that patients can benefit from outside the telemedical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…This is in line with the findings of a qualitative study conducted within The Virtual Hospital, as the participants in the study experienced that virtual contacts were more focused compared with the interaction with the health professionals during conventional hospital admission (Emme et al . ). Nevertheless, health professionals should be aware of the changes that telemedical communication brings about, such as amplification of nonverbal behaviour and the significance of the tone of voice (Bulik ).…”
Section: Discussionmentioning
confidence: 97%
“…This is in line with the findings of a qualitative study conducted within The Virtual Hospital, as the participants in the study experienced that virtual contacts were more focused compared with the interaction with the health professionals during conventional hospital admission (Emme et al . ). Nevertheless, health professionals should be aware of the changes that telemedical communication brings about, such as amplification of nonverbal behaviour and the significance of the tone of voice (Bulik ).…”
Section: Discussionmentioning
confidence: 97%
“…The use of TM represents an intervention in the patient's daily life and changes the way the patient relates to healthcare services. Therefore, more studies are needed to gain precise knowledge about the patient's lived experience related to the use of TM equipment (Emme et al., ; Greenhalgh et al., ; Ure et al., ) and to learn about what matters to the user of TM technology (Greenhalgh, Procter, Sugarhood, Hinder, & Rouncefield, ; Greenhalgh et al., ). Because people with COPD live with symptoms that present a significant burden in daily life, it is particularly important to have knowledge of how TM affects their life situation.…”
Section: Introductionmentioning
confidence: 99%
“…These factors align closely with previous studies on the delivery of health-related products evidenced through increasing Web-based self-help resources [ 4 ], effective delivery of psychological interventions [ 68 ], and their ability to reach rural areas within diverse populations and settings [ 6 ]. The body of eHealth research is expanding with studies across different patient groups, using different technologies/interventions, and focusing on different outcomes [ 69 - 73 ]. In their interpretive review of the literature on consumer eHealth, Hordern et al [ 74 ] identified five broad usage themes: (1) peer-to-peer online support groups and health-related virtual communities, (2) self-management/self-monitoring applications, (3) decision aids, (4) the personal health record, and (5) Internet use.…”
Section: Discussionmentioning
confidence: 99%